27 Inherited cardiomyopathy conditions clinic in district general hospital improves esc guidelines implementation and management of patients with hypertrophic cardiomyopathy. (4th June 2021) - Luo, Elton; Chan, Kenneth; Basu, Joyee; Tilling, Lindsey; Balkhausen, Katrin; Bull, Sacha
Abstract : Background: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiomyopathy and is frequently encountered in clinic. In many district general hospitals (DGH), the condition is frequently managed in general cardiology clinics with a small proportion referred to dedicated Inherited Cardiomyopathy Conditions (ICC) clinic in tertiary centres for complex treatments. We hypothesised that management of HCM patients would be improved by introduction of a dedicated ICC clinic at our district general hospital. Purpose: The purpose of the study was to evaluate the impact on patient management in a dedicated ICC clinic at our district general hospital. The outcome was determined by assessing adherence to the European Society of Cardiology (ESC) HCM guidelines before and after introduction of this clinic, hospital admission and mortality. Methods: We retrospectively reviewed the clinic records of patients with a diagnosis of HCM seen in the general cardiology clinic. A dedicated ICC clinic was established and the patient records of those with HCM assessed in the ICC clinic over a 6-month period were also reviewed. Patient assessment and management were evaluated against ESC recommendations, including clinical risk stratification (symptoms review, ambulatory blood pressure monitoring, 48-hour Holter monitoring, sudden cardiac death (SCD) risk assessment); imaging assessment by echocardiography and cardiac magnetic resonance (CMR); and patient counselling (exercise, genetic, and family counselling). Patient outcomes at 2-years were evaluated, including hospital admissions from cardiac causes (arrhythmia, stroke, chest pain, heart failure); new onset heart failure; SCD and all-cause mortality. Results: Demographics were similar for HCM patients assessed in the ICC clinic (n=62, mean age 61±13), and general cardiology clinic prior to the introduction of lCC clinic (n=24, mean age 61±17). There were significant improvements in risk stratification by clinical assessment of symptoms, holter monitoring, as well as formal SCD risk evaluation ( table 1 ) . There was better compliance with ESC recommendations in imaging assessments; more patients underwent CMR and left ventricular outflow tract (LVOT) assessment in echocardiography in the ICC clinic cohort ( table 2 ) . None of the patients in either cohort met the clinical endpoint of SCD. Hospital admission from cardiac causes at 2-years was significantly lower in the patients assessed in ICC clinics ( table 2 ) . Conclusion: In this HCM cohort, introduction of a local ICC clinic led to improved patient care through better adherence to ESC HCM guidelines in particular with respect to clinical assessment, imaging and risk stratification as well as reduced hospitalisations from cardiac causes. Conflict of Interest: None